Towards designing a multipurpose cybercrime intelligence framework - Nouh, M; Nurse, J; Goldsmith, M (IEEE, 2016)
With the wide spread of the Internet and the increasing popularity of social networks that provide prompt and ease of communication, several criminal and radical groups have adopted it as a medium of operation. Existing literature in the area of cybercrime intelligence focuses on several research questions and adopts multiple methods using techniques such as social network analysis to address them. In this paper, we study the broad state-of-the-art research in cybercrime intelligence in order to identify existing research gaps. Our core aim is designing and developing a multipurpose framework that is able to fill these gaps using a wide range of techniques. We present an outline of a framework designed to aid law enforcement in detecting, analysing and making sense out of cybercrime data.